2012
DOI: 10.1007/s13592-012-0145-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome size diversity in stingless bees (Hymenoptera: Apidae, Meliponini)

Abstract: The first studies on the genome size of stingless bee species showed a range from 0.27 pg (Melipona subnitida and Melipona quadrifasciata) to 1.38 pg (Melipona capixaba). Considering this variation, we quantified the DNA content of 26 species of Meliponini, in order to provide input for future comparative studies in this tribe. Haploid genome size (1C) estimates, using flow cytometry analyses (FCM), ranged from 0.26±0.003 pg (Paratrigona subnuda) to 0.98±0.023 pg (Melipona flavolineata), with an average of 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Genome size is another trait useful in comparative studies in a variety of taxonomic levels (Gregory and Shorthouse 2003, Tsutsui et al 2008, Tavares et al 2012). Such information is also important to clarify the relationship between variation in genome size and chromosome number (Tsutsui et al 2008, Cardoso et al 2012, Jacobson et al 2012), and direct the selection of species for genome sequencing projects (Hardie et al 2002, Gregory 2005, Geraci et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genome size is another trait useful in comparative studies in a variety of taxonomic levels (Gregory and Shorthouse 2003, Tsutsui et al 2008, Tavares et al 2012). Such information is also important to clarify the relationship between variation in genome size and chromosome number (Tsutsui et al 2008, Cardoso et al 2012, Jacobson et al 2012), and direct the selection of species for genome sequencing projects (Hardie et al 2002, Gregory 2005, Geraci et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, only Lopes et al [37] and Tavares et al [35,36] have estimated the genome size of Scapitotrigona xantotricha, and found a difference in the values recorded for males and females. This is probably because bees, like ants, have a haplodiploid sex determination system, with haploid males and diploid females (workers and queens).…”
Section: Internal Standards Lysis Buffers and Tissuementioning
confidence: 96%
“…These standards are Drosophila melanogaster and Scaptotrigona xantotricha (e.g. [6,14,[34][35][36] [37]. Both these standards were tested so that we could determine the internal reference standard for estimating the nuclear genome size of the ants collected in the present study.…”
Section: Evaluation Of the Internal Standards And Lysis Buffersmentioning
confidence: 99%
See 2 more Smart Citations